Moving rubber to a better place - and extracting rents from credit constrained farmers along the way - Thomas Kopp; Bernhard Bümmer (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
While traders of agricultural products are known to often exercise market power, this power has rarely been quantified for developing countries. In order to derive a measure, we estimate the traders' revenue functions and calculate the Marginal Value Products directly from them. We subsequently find determinants affecting their individual market power. An exceptional data set with detailed information on the business practices of rubber traders in Jambi, Indonesia is employed. Results show that market power at the traders' level exists and is substantial. This market power is amplified in situations of extreme remoteness, and weakens with increasing market size.
urn:nbn:de:gbv:7-webdoc-3948-1
Keywords: F14; Q13; L14; 330; Trader Survey; Market Power; Lerner Index; Marginal Value Products; Indonesia; Marktmacht; Einnahmen; Produktionsfunktion; Landhandel; Kautschuk; Indonesien